2006
DOI: 10.1111/j.1463-1318.2005.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiotherapy on different histopathological types of rectal carcinoma

Abstract: Mucinous carcinoma was associated with a lower response to pre-operative chemo-radiotherapy in this group of rectal carcinoma patients. Further studies are needed to determine its prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 40 publications
8
40
1
1
Order By: Relevance
“…In this study, the survival data were collected from various research, through meta-analysis, the HR value was 1.06 (CI: 1.04-1.08), suggesting the prognosis was poor in mucinous adenocarcinoma patients, although the difference of prognosis was not obvious, the HR value was only 1.06, there were still significant difference (P<0.001); therefore, we believe that mucinous adenocarcinoma is an independent prognostic risk factor for colorectal cancer. This result may be associated with reducing the sensitivity of radiotherapy and chemotherapy by mucinous adenocarcinoma (Negri et al, 2005;Sengul et al, 2006). We should pay more attention to the mucinous adenocarcinoma patients, the patients who were confirmed should be performed radical resection, and expanding the dissection range of lymph node, these organs which have been infiltrated should be performed resection too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the survival data were collected from various research, through meta-analysis, the HR value was 1.06 (CI: 1.04-1.08), suggesting the prognosis was poor in mucinous adenocarcinoma patients, although the difference of prognosis was not obvious, the HR value was only 1.06, there were still significant difference (P<0.001); therefore, we believe that mucinous adenocarcinoma is an independent prognostic risk factor for colorectal cancer. This result may be associated with reducing the sensitivity of radiotherapy and chemotherapy by mucinous adenocarcinoma (Negri et al, 2005;Sengul et al, 2006). We should pay more attention to the mucinous adenocarcinoma patients, the patients who were confirmed should be performed radical resection, and expanding the dissection range of lymph node, these organs which have been infiltrated should be performed resection too.…”
Section: Discussionmentioning
confidence: 99%
“…However, some other findings showed that mucinous adenocarcinoma was an independent prognostic risk factor (Kanemitsu et al, 2003;Catalano et al, 2009;Ghabeljoo et al, 2011). Some studies showed that mucinous adenocarcinoma might reduce the sensitivity of radiotherapy and chemotherapy in recent years (Negri et al, 2005;Sengul et al, 2006). At present, there are few studies about mucinous adenocarcinoma in China, and most studies suggested that the patients with mucinous adenocarcinoma had late stage and poor prognosis (Songqing et al, 2002;Miao et al, 2005;Safaee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In some of the patients, however, MLs are induced by nCRT in rectal cancer tissue (5)(6)(7)(8)(9)(10)(11)(12). In patients who receive nCRT, the incidence of mucinous carcinoma is relatively high, ranging from 13% to 24% (6,8,11).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with mucinous carcinoma have been reported to have a poor response to nCRT, as well as poor outcomes. In some patients, however, nCRT may induce the formation of mucin lakes (MLs) in rectal cancer tissue (5)(6)(7)(8)(9)(10)(11)(12). The ability to determine whether MLs are induced or originally exist in resected specimens would be of great clinical significance.…”
mentioning
confidence: 99%
“…None of the mucinous tumour achieved complete response, but almost half were down-staged by one stage. Sengul et al [40] reported a statistically significant difference in tumour regression grade (TRG) between the two subtypes and a much smaller decrease in T and N staging. However, only 16 patients were studied and the small numbers may account for the results.…”
Section: Radiological Diagnosis and Measuring Responsementioning
confidence: 99%